2021
DOI: 10.3390/ma14206199
|View full text |Cite
|
Sign up to set email alerts
|

Fabricated CAD/CAM Post-Core Using Glass Fiber-Reinforced Resin Shows Innovative Potential in Restoring Pulpless Teeth

Abstract: The prevention of root fractures of pulpless teeth is an important clinical issue to maintain healthy teeth through lifetime. The aim of this study was to examine a clinically effective treatment method for strengthening vulnerable pulpless teeth using CAD/CAM (computer-aided design/computer-aided manufacturing) fiber-reinforced post-core by conducting a fracture resistance test. A post-core made with a fiber-reinforced resin disk TRINIA (TR, SHOFU, Kyoto, Japan) was fabricated using a CAD/CAM system. The fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…These unique properties work together to maintain its durably high strength during extended intraoral use periods. The strength of dental polymeric materials has been reported to increase with the incorporation of glass fibers, as shown in previous studies [44][45][46]. Previous studies by Suzaki et al demonstrated the superior flexural strength of CAD/CAM FRP, particularly if the fiber directions were identified [44,47], which is supported by the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These unique properties work together to maintain its durably high strength during extended intraoral use periods. The strength of dental polymeric materials has been reported to increase with the incorporation of glass fibers, as shown in previous studies [44][45][46]. Previous studies by Suzaki et al demonstrated the superior flexural strength of CAD/CAM FRP, particularly if the fiber directions were identified [44,47], which is supported by the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The strength of dental polymeric materials has been reported to increase with the incorporation of glass fibers, as shown in previous studies [44][45][46]. Previous studies by Suzaki et al demonstrated the superior flexural strength of CAD/CAM FRP, particularly if the fiber directions were identified [44,47], which is supported by the results of the current study. This is in accordance with the results of a recent study by Babaier et al that concluded the higher flexural strength of two similar FRP CAD/CAM materials (ranging between almost 400-500 MPa) compared to PEEK (around 200 MPa) [48]._NCH blocks (GR) are relatively new and marketed for their superior mechanical and esthetic properties, requiring no firing or lamination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fully digital method simplifies and shortens clinical and laboratory procedures. Post and core restorations with aesthetic materials have been studied in the literature [4,5]. As a result, the accuracy of the fitment to the walls of the root canal and the endurance to chewing forces by various stimulators have been established.…”
Section: Discussionmentioning
confidence: 99%
“…Metal alloys, ceramics based on zirconium dioxide, lithium disilicate ceramics, fibre‐reinforced composites, PEEK, nano‐ceramic resin composites, hybrid ceramics etc. can be processed by milling 11–13 …”
Section: Introductionmentioning
confidence: 99%